Discovery of 2, 3′-diindolylmethanes as a novel class of PCSK9 modulators. Issue 16 (15th August 2019) - Winston-McPherson, Gabrielle N.; Xie, Haibo; Yang, Ka; Li, Xiaoxun; Shu, Dongxu; Tang, Weiping
Graphical abstract: Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) promotes the degradation of low density lipoprotein receptor (LDLR). Anti-PCSK9 agents have been approved for the treatment of hypercholesterolemia. We recently discovered a series of small-molecule PCSK9 modulators that contains a relatively small pharmacophore of 2, 3′-diindolylmethane with molecular weights around only 250. These molecules can significantly lower the amount of PCSK9 protein in a cell-based phenotypic assay. Our SAR studies yielded compound 16 with a IC50 -value of 200 nM. No obvious cytotoxicity was observed at concentrations below 50 µM.